Depresión y riesgo suicida en estudiantes de educación secundaria de la Institución Educativa Rosa Agustina Donayre de Morey Iquitos 2024 - Vásquez Vásquez, Jeennifer Diane (2025)
The main objective of the research was to determine if there is an association between depression and suicide risk in secondary school students at the Rosa Agustina Donayre de Morey Educational Institution Iquitos 2024, the study used is quantitative and non-experimental design, cross-sectional correlational, with a population and sample of 224 students. The technique used was the survey and the instruments used are: The Zung depression scale and the Plutchik Suicide Risk Scale. The results obtained regarding the depression variable allow us to observe that 84,4% report the absence of depression, 12,9% presented mild depression and 2,7% moderate depression. Regarding suicidal risk, it was possible to identify 10,7% without suicidal risk, 55,4% at low risk and 33,9% of students with high suicidal risk. For the hypothesis test, the chi square statistic (X2) was used with continuity correction 50,6 gl 4 p = 0,001 α < 0.05. It is therefore concluded that there is a significant statistical association between depression and suicide risk among third- and fourth-grade secondary school students at the Rosa Agustina Donayre de Morey Educational Institution, Iquitos 2024.